2010
DOI: 10.1108/14725961011078990
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting housing maintenance cost in Malaysia

Abstract: Purpose -It has been found that the cost for housing maintenance is relatively high due to poor maintenance practices. This paper aims to determine and identify the factors contributing to rising maintenance costs. Design/methodology/approach -A quantitative approach was adopted that sought to gather factual data using the approach taken by El-Haram and Horner. The research first identified the critical factors through a literature review. A total of Eighty questionnaires were then distributed to relevant resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
167
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(184 citation statements)
references
References 29 publications
10
167
2
5
Order By: Relevance
“…The list of factors are analysed through a theoretical part that discusses on operation and maintenance cost of stratified buildings. Table 3 lists down all the factors that affecting operation & maintenance costs by El-Haram & Horner [39], Ali et al [3], Assaf et al [40] and Al-Hammad et al [1]. El-Haram & Horner [39] and Ali et al [3] directly highlight on contributing factors affecting operation and maintenance costs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The list of factors are analysed through a theoretical part that discusses on operation and maintenance cost of stratified buildings. Table 3 lists down all the factors that affecting operation & maintenance costs by El-Haram & Horner [39], Ali et al [3], Assaf et al [40] and Al-Hammad et al [1]. El-Haram & Horner [39] and Ali et al [3] directly highlight on contributing factors affecting operation and maintenance costs.…”
Section: Methodsmentioning
confidence: 99%
“…Maintenance and operating cost is one of the major components of housing cost and contributes one third to one half of total cost depending on the type of housing such as condominium, apartment, flat and others [3,29]. It has been reported that between 70% and 85% of the building maintenance and operation costs can be influenced during the design stage.…”
Section: Operations and Maintenance Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical performance is defined as the totality of features required by a project or service to satisfy a given specification, need or fitness for purpose (Ali et al, 2010;Chan and Chan, 2004). Technical performance is the project guarantee that convinced both the client and the end-users that the specification was adhered to during construction.…”
Section: Introductionmentioning
confidence: 99%